Penggunaan Afiksasi dalam Proses Pembentukan Istilah Medis Bahasa Indonesia - Shifa Hendariyunisha; Eri Kurniawan; Ruswan Dallyono (Departement of Mathematics Education, 2024)
Medical terminology, previously reserved for professionals, has become increasingly prevalent in everyday discourse, particulary following the COVID-19 pandemic. The emergence of these terms is not spontaneous; rather, they are meticulously crafted by experts within their respective fields. This research examines the formation of Indonesian medical terms, with a specific focus on affixation. The purpose of this research is to find out the affixation process used in Indonesian medical terms. The method used in this research is descriptive qualitative with the data source of medical terms found on the Halodoc platform. The choice of Halodoc is aligned with the rising popularity of health applications during the pandemic. The result shows that from 1492 medical terms data, 202 words (13.5%) are formed through affixation process. There are foreign language affixation processes (prefixes and suffixes) and Indonesian language affixation processes (prefixes, suffixes, confixes). Foreign language affixation shapes the term to be more complex, while the use of Indonesian affixation only changes the word class. The results of this study are also expected to represent the characteristics of the Indonesian language in forming words, especially medical terms.